Cytotoxic effects of catechols to glial and neuronal cells - Ramon Santos El-Bachá (Frontiers in Cellular Neuroscience, 2015)
Catechols are compounds that autoxidises under physiological conditions leading to the formation of reactive oxygen species (ROS), semiquinones, and quinones. These molecules can be formed in organisms because of the metabolism of exogenous aromatic substances, such as benzene. However, there are several important endogenous catechols, which have physiological functions, such as catecholamines. Furthermore, several pharmacological agents are catechols, such as apomorphine, or can be metabolised to generate these compounds. In this presentation we will show that apomorphine can unspecifically bind to proteins during its autoxidation, a phenomenon that is inhibited by thiols. Brain endothelial cells and glial cells express xenobiotic-metabolising enzymes as components of the metabolic blood-brain barrier in an attempt to protect the central nervous system against drugs. Since UDP-glucuronosyltransferases (EC 2.4.1.17) are among these enzymes, we investigated the ability of brain microsomes to conjugate catechols with glucuronate. Despite the fact that 1-naphtol could be glucuronidated in the presence of brain cortex microsomes, the same was not observed for most of catechols that were tested. Therefore, this is not the main mechanism used to protect the brain against them. Indeed, catechols may inhibit other xenobiotic-metabolising enzymes. We showed that apomorphine inhibited the cytochrome P450-dependent dealkylation activity. The production of ROS and reactive quinones, as well as their effects on protein functions, seems to be involved in the cytotoxicity of catechols. Glial cells are more resistant than neuronal cells. Apomorphine was more toxic to rat neurons than to rat C6 glioma cells. 1,2-Dihydroxybenzene (catechol) killed human GL-15 cells with an EC50 of 230 uM after 72 h, a effect that was significantly inhibited by superoxide dismutase (EC 1.15.1.1). Another mechanism that we found to be involved in catechol cytotoxicity is the inhibition of FADH2-linked mitochondrial respiration. 3-Methylcatechol, which is a metabolite of toluene, not only inhibited the mitochondrial respiration, this also induced peroxidation of biomolecules. The cytotoxic effect of catechols is due to its ability to reduce other molecules with two electrons. When catechol was linked to ruthenium, only one electron can be used to reduce other molecules. This change on the redox property was associated with a diminished cytotoxic effect of the complex to glial cells compared with the free catechol. The treatment of rat neuroblastoma N2a cells and human glioblastoma GL-15 cells with catechol induced a depletion of reduced glutathione after 24 hours, leading to apoptosis after 72 hours. Another observed effect was nuclear condensation and DNA fragmentation. This is important to understand the cytotoxic effects of catechol to glial and neuronal cells because they may be involved in the mechanisms of neurodegenerative disorders, specially Parkinson's disease.